Biphasic insulin analogues in type 2 diabetes: Expert panel recommendations [Tip 2 Diyabette Bifazik Analog İnsülinler: Bir Tedavi Örneǧi ile Uzman Paneli Görüşleri] - (:unkn) unknown (Turkiye Klinikleri, 2011)
Recently, the prevalence of type 2 diabetes has reached pandemic levels all over the world, and the problem is still growing. Type 2 diabetes is a progressive disease, in which insulin resistance and decrease in beta cell function accompany obesity. Early disorder, which ensues in clinical progression of the disease, is the defect of early phase insulin secretion. Patients have already lost approximately half of their beta cell reserve at the time of diagnosis. Aims of type 2 diabetes treatment are to eliminate hyperglycemia caused by insufficient insulin secretion and/or insulin resistance, to slow down beta cell destruction/depletion, to improve concomitant metabolic problems and to prevent complications. In treatment algorithms, insulin is evaluated as a replacement therapy at the following stage after life style changes (medical nutrition therapy, exercise) and oral anti-diabetic drugs (OADs) options. Since beta cell depletion is present at initial stages of the disease, it transforms insulin therapy into an earlier approach in treatment stages. Premixed insulin forms are one of the proposed treatment options in patients with hyperglycemia that is not controlled by OADs. These types of insulins are developed to meet both basal and postprandial insulin requirements of patients. Currently, premixed human insulin forms are replaced by analogue insulin forms, which can mimic the physiological secretion in more acceptable manner. Biphasic analogue insulin is one of the readily available pre-mixed analogue insulin forms, an example of this, Biphasic Insulin aspart 30 which is the one of the premixed analoge insulin forms, contains 30% insulin aspart and 70% protaminated insulin aspart. Consensus recommending the individualized approach in insulin therapy implies that physicians should have more detailed information about the use of different insulin forms. Although a global consensus report about initiation, titration and intensification and the use of Biphasic Insulin Aspart 30 treatment has been published recently, these types of guidelines cannot always respond to all of the local requirements. Therefore, it is aimed to prepare a guideline to facilitate the use of Biphasic Insulin Aspart 30 in the right patient, at the right time and in the right manner, as well as to help the physicians. A guideline, aiming to contain current evidences and to meet local requirements, was developed in May and June 2010 by an expert panel composed of experienced endocrinologists working at different parts of Turkey. The guideline includes initial treatment, optimization of initiation dose, and intensification of Biphasic Insulin Aspart 30 during the disease progression. Although previously published global guidelines about initiation, intensification, dose division, dose addition and combination of Biphasic Insulin Aspart 30 with OADs is in applicable situation in general, the content is enlarged by adding some special conditions. Administration information presented in this article forms simply a suggestion rather than a strict recommendation. Since the treatment of every diabetic patient should be individualized, suggestions of this guideline do not have any obligatory power on physicians.
Keywords: Biphasic Insulin Aspart 30; Insulin analogue; Insulin intensification; Premixed insulin